Automotive fundamentals automative basics (New Jersey : A Shopware Production, 2004)
this CD-ROM provides a through automative orientation, introducing the major mechanical, hydrolic and electrical systems of vehicles and identifying the purpose, function and operation of each system covered.
System requirements: 200 MHz processor, 32 MB RAM (64MB preferred), 4 x cd-rom drive, 800 x 600 display with 256 colors, soundcard and speakers or headphones, keyboard, mouse, QUICKTIME 4 or higher, Adobe Acrobat Reader.
Keywords: Automobiles; Motor vehicles; Mechanical engineering